The status of liver enzymes in patients of newly diagnosed human immuno-deficiency virus and their correlation with CD4 counts in a tertiary centre of North Eastern region of India - Gupta, Poonam; Kalra, Archit; Chaurasia, Ajeet K.; Mathur, Manoj; Kumar, Satyam; Singh, Kamalendra; Varma, Sharad (International Journal of Advances in Medicine, 2025)
Background: Liver dysfunction is a common complication in human immunodeficiency virus (HIV)-infected individuals due to factors like co-infections, antiretroviral therapy (ART) toxicity, and immune dysregulation. Evaluating liver enzyme abnormalities can help predict disease progression and guide therapy. Methods: A cross-sectional study was conducted on 100 newly diagnosed HIV-positive individuals. Liver function was assessed using serum glutamate-oxaloacetate transaminase (SGOT) and serum glutamate-pyruvate transaminase (SGPT) levels, and immune status was measured by CD4 counts. The correlation between liver enzymes and CD4 levels was analyzed statistically. Results: The study population had a male predominance (70%) with a mean age of 37.29±13.01 years. A weak positive correlation was found between CD4 count and both SGOT and SGPT levels. Liver enzyme derangements were more prominent in patients with lower CD4 counts, indicating advancing immunosuppression. Conclusion: This study highlights the universally raised liver enzymes in all the patients of newly diagnosed HIV indicating hepatic injury by the virus itself. Medical literature regarding the probable mechanism is all together lacking. There was minimal positive correlation found between CD4 count and liver enzymes.